0304 Characterizing age and sex-related changes in sleep EEG K-complex morphology in 3, 909 individuals. (25th May 2022) - Valencia, Daphne; Schoenholz, Reagan; Bischoff, Giles; Mullins, Anna; Kam, Korey; Fakhoury, Ahmad; Varga, Andrew; Rapoport, David; Ayappa, Indu; Mazumdar, Madhu; Berkalieva, Asem; Parekh, Ankit
Abstract: Introduction: K-complexes are hallmarks of sleep stage N2 and are thought to be associated with two distinct roles that serve as either or both, a sleep protective mechanism or a cortical arousal response. K-complexes and their morphological features (number, delta surrounding K complexes, etc.) have been implicated in sustained attention as well as in Alzheimer's disease wherein a decline in the number of K-complexes appeared to discriminate diseased individuals from healthy controls. Yet, age and sex-related changes in K-complex morphology are not well-known. Methods: We analyzed data from the Sleep Heart Health Study (SHHS) to understand age- and sex-related changes in K-complex morphology. The SHHS is a cohort study comprised of 5, 804 men and women aged 40 and older aimed at investigating the cardiovascular consequences of sleep-disordered breathing. K-complex (on C3/A2) features were quantified using previously published and validated open-source algorithm (DETOKS; Parekh et. al. J. Neurosci Meth. 2015). Three features of K-complexes were studied: number of K-complexes (density), delta (∆SWAK) and alpha (∆alphaK) surrounding K-complexes. Results: Of the 5, 804 studies available, 3, 909 that had at least 6h of usable EEG were analyzed (mean = 62±11 yrs., range [40-90 yrs.], 53%female). With aging, K-complex density and (rho=-0.1, p<0.0001), ∆SWAK (rho=-0.2, p<0.0001) were inversely associated with age, while ∆alphaK (rho=0.1, p<0.01) was significantly positively associated with age. The inverse association of K-complex density with age was greater in men compared to women (rhomen=-0.3, p<0.0001, rhowomen=-0.1, p<0.01). Women had greater K-complex density compared to men (1.8[1.3-2.4] vs. 1.3[0.9-1.8], median[IQR]; std. mean diff =0.4). The changes in K-complex morphology with age remained significant after controlling for OSA severity. Conclusion: Age is associated with decline in K-complex morphology such that K-complex density and delta activity surrounding K-complexes declines whereas alpha activity surrounding K-complexes increases. An age-related decline in delta activity surrounding K-complexes and an increase in alpha activity surrounding K-complexes is consistent with the potential role for these features in either sleep-state maintenance or arousal responsiveness. Whether the decline in K-complex morphology seen here with aging, and its interaction with sex-related differences, is accelerated in neurodegenerative disorders such as AD remains to be tested. Support (If Any): Support: NIH K25HL151912, AASMFoundation BS-233-20